Lessons from Corviale: from the critical factors of Public Housing Plans towards a methodology for urban regeneration - Di Giovanni, C. (Italian Journal of Planning Practice, 2020)
This paper is part of Urban Studies PhD research that seeks new approaches of urban regeneration in ongoing interventions in social housing neighbourhoods in Italy and Portugal. Corviale is here taken as case study assessed with a ‘zoom-out methodology’, that means to expand the analysis from the case study to Rome regarding the construction of the ‘public city’ and the regeneration of public housing neighbourhoods. On one hand, Corviale allows comprehension of the critical factors of Public Housing Plan (PEEP) in Rome: large dimensions, massive housing concentration, high execution speed, incapacity of the public management, under-use of the public assets and unfinished services. On the other hand, the interventions featured in the case study display a strategy for the urban regeneration through three points: densification of the existing housing stock; solution to the squatting that does not involve forced evictions; and participation by way of the “Laboratorio di Città Corviale”. The case study sheds light on the past stages of the Italian public housing and recognises a model for urban regeneration of public housing. The research identifies public housing neighbourhoods as an ideal ground of investigation and action to develop new methods of urban planning.